2014
DOI: 10.12717/dr.2014.18.4.301
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Distribution of Nesfatin-1/NUCB2 in Mouse

Abstract: Nesfatin-1, an anorexic nucleobindin-2 (NUCB2)-derived hypothalamic peptide, controls appetite and energy metabolism. Recent studies show that nesfatin-1/NUCB2 is expressed not only in the brain but also in gastric and adipose tissues. Thus, we investigated the distributions of nesfatin-1/NUCB2 in various tissues of male and female mice by real-time PCR, western blotting, and immunohistochemical staining. Real-time PCR analyses showed that NUCB2 mRNA was predominantly expressed in the pituitary and at lower le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
5
41
0
1
Order By: Relevance
“…In rodents, NUCB2/nesfatin-1 is highly expressed in the appetite-control hypothalamic nuclei, including the paraventricular (PVN), supraoptic (SON), arcuate (Arc), and lateral hypothalamic area (LHA). It is extensively colocalized with neuropeptides involved in the regulation of hunger, satiety, and other homeostatic functions, such as oxytocin, vasopressin, melanin-concentrating hormone (MCH), and cocaine- and amphetamine-regulated transcript (CART) [3, 5-10]. In the periphery, NUCB2/nesfatin-1 has been detected in gastric mucosa, adipose tissue, pancreatic islets, and testes as well as in cerebrospinal fluid and plasma in animals and humans [9-19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, NUCB2/nesfatin-1 is highly expressed in the appetite-control hypothalamic nuclei, including the paraventricular (PVN), supraoptic (SON), arcuate (Arc), and lateral hypothalamic area (LHA). It is extensively colocalized with neuropeptides involved in the regulation of hunger, satiety, and other homeostatic functions, such as oxytocin, vasopressin, melanin-concentrating hormone (MCH), and cocaine- and amphetamine-regulated transcript (CART) [3, 5-10]. In the periphery, NUCB2/nesfatin-1 has been detected in gastric mucosa, adipose tissue, pancreatic islets, and testes as well as in cerebrospinal fluid and plasma in animals and humans [9-19].…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have demonstrated NUCB2/nesfatin-1 distribution in hypothalamic nuclei and brain areas with established roles in energy homeostasis, neuroendocrine functions, and body weight regulation [3, 5-10, 33]. However, NUCB2/nesfatin-1 protein expression in the human hypothalamus remains to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…pancreas and testis (Gonzalez et al 2009, Shimizu et al 2009b, Ramanjaneya et al 2010, Kim et al 2014. Within the central nervous system (CNS), Nucb2 mRNA is present, for example, in the hypothalamus and brainstem (Oh-I et al 2006, Brailoiu et al 2007) (for more details we refer to the respective sections).…”
Section: Nucb2 and Nesfatin-1: Expression Processing And Releasementioning
confidence: 99%
“…Alternatively, other enzymes, for example, the cell surface membrane-bound protein furin, which cleaves at the same general motif as the PCs, might be involved in NUCB2 processing (Seidah & Prat 2002). In most rodent tissues studied, for example, gastric mucosa, pancreas, pituitary gland and testis, either only the precursor NUCB2 or indistinguishable NUCB2/nesfatin-1 was detected , Kim et al 2014. However, nesfatin-1, the amino terminal putative cleavage product of NUCB2, was unambiguously identified in the hypothalamus and CSF of rodents (Oh-I et al 2006) and also in human plasma (Tsuchiya et al 2010).…”
Section: Nucb2 and Nesfatin-1: Expression Processing And Releasementioning
confidence: 99%
See 1 more Smart Citation